Establishment of stable and secretable Tatκ-GFP recombinant protein: a preliminary report of promoter methylation in 293t cell line - Zariyantey Abd Hamid,; Fazlina Nordin,; Rajaa Norazireen Raja Ahmad,; Balqis Mat Rashid,; Ubashini Vijakumaran, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Induced pluripotent stem cells (iPSC) is a novel technology useful for therapeutic and research applications. To date, iPSCs is produced through genetic modification that can promote mutation; making it harmful for therapeutic use. Therefore, application of non-genetic modification through direct delivery of recombinant proteins aided by protein transduction domain (PTD) enable a safer production of iPSC. This study is aimed to establish a stable production of secretable recombinant protein via recombination of green fluorescence protein (GFP) and a novel PTD peptide, namely TATκ-GFP. 293Tcell line was transfected with 20 μg/ml of TATκ-GFP plasmid and the stably transfected 293T cells were then cultured for 54 days to determine the stability of expression and secretion of TATκ-GFP recombinant protein in prolonged culture. Methylation at the CMV promoter of the TATκ-GFP plasmid was investigated following treatment of transfected cells with 3 μM/mL of demethylation agent, namely 5-Azacytidine for 72 h in three cycles. Flow cytometry analysis demonstrated a transfection efficiency of 9.33% and successful secretion of TATκ-GFP proteins into the culture medium as analysed by Western blot at 72 h post-transfection. However, the transfected cells exhibited a decreasing level of GFP expression and secretion following prolonged culture with notable stability that only sustained for two weeks. 5-Azacytidine-treated cells showed a slight increase of GFP expression compared to non-treated control, suggesting possible promoter methylation which could cause instability of TATκ-GFP expression. Conclusively, promoter methylation should be considered for future establishment of iPSCs as it could inhibit stable expression and secretion of recombinant proteins.